Cutting performance and contact behavior of partial-wear TBM disc cutters: A laboratory scale investigation. (July 2022) - Sun, Ruixue; Mo, Jiliang; Zhang, Mengqi; Su, Yemao; Zhou, Zhongrong
Highlights: Rock cutting performance and contact behavior of partial-worn cutters are studied. Cutting forces, rock fragments, cutter acceleration are analyzed. Partial-worn cutters are able to break rock but energy consumption increases. Above differences are attributed to motion modes and surface geometry changes. This work provides theoretical support for monitor system of cutter partial-wear. Abstract: The rock cutting performance and cutter-rock contact behavior of partial-worn cutters are investigated via scaled rock cutting experiments. The results reveal that the partial-wear of the cutter reduces the normal force, while the tangential force increases. Changes are also observed in the rock breaking mechanism. Although the rock breaking capacity of the partial-worn cutters is not significantly reduced, the increase of volume ratio of the rock powder results in a rise in specific energy, indicating that the energy utilization of the partial-worn cutters is relatively low. In addition, plastic deformation and abrasive wear are observed on the partial-worn cutter surface. The changes of motion modes and surface geometry play a key role in the above-mentioned phenomena.